Effect of proton pump inhibitor on microbial community, function, and kinetics in anaerobic digestion with ammonia stress. (January 2021) - Yu, Dawei; Zhang, Qingqing; De Jaegher, Bram; Liu, Jibao; Sui, Qianwen; Zheng, Xiang; Wei, Yuansong
Graphical abstract: Highlights: The proton pump inhibitor mitigated ammonia inhibition by the proton mechanism. Metabolic pathways of acetate compared at different dosages of proton pump inhibitor. Gompertz and Gaussian processes modeled deterministic kinetic and random effect. The proton pump mechanism of ammonia inhibition was refined with metagenomics. PPI dose showed potential in investigating molecular mechanism of ammonia inhibition. Abstract: The proton pump is a convincing mechanism for ammonia inhibition in anaerobic digestion, which explained how the ammonia accumulated intercellularly due to diffusion of free ammonia. Proton pump inhibitor (PPI) was dosed for mitigating the accumulation in anaerobic digestion with ammonia stress, with respect to kinetics. Results show PPI inhibited β-oxidation of fatty acids by targeting ATPase in anaerobic digestion with ammonia stress. Alternatively, PPI stimulated syntrophic acetate oxidization. Random forest located key genera as syntrophic consortia. Methane increased 18.72 ± 7.39% with 20 mg/L PPI at the first peak, consistent with microbial results. The deterministic Gompertz kinetics and stochastic Gaussian processes contributed 97.63 ± 8.93% and 2.37 ± 8.93% in accumulated methane production, respectively. Thus, the use of PPI for anaerobic digestion allowed mitigate ammonia inhibition based on the mechanism of proton pump, facilitate intercellularly ammonia accumulation, stimulate syntrophic consortia, and eliminate uncertainty of process failure, which resulted in efficient methane production under ammonia stress.